PENGARUH KONTEN TIKTOK @GALIH.MAKEUPARTIS TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKEUP MAHASISWI S1 PENDIDIKAN TATA RIAS UNIVERSITAS NEGERI SURABAYA - Retha, Mella Elva; Nia Kusstianti; Nieke Andina Wijaya; Mutimmatul Faidah (Jurnal Tata Rias, 2025)
The development of digital technology has transformed the way consumers obtain information and form preferences regarding makeup products. Social media, particularly TikTok, has become a strategic platform for beauty influencers to share educational content, reviews, and product recommendations. This study aims to determine whether there is an influence, and to what extent, the TikTok content of @galih.makeupartis affects the purchasing decisions of undergraduate students majoring in Beauty Education at Universitas Negeri Surabaya. This research employs a quantitative approach with an associative research type. Data were collected through questionnaires distributed to 55 respondents and analyzed using a simple linear regression test. The results show that the TikTok content of @galih.makeupartis has a significant influence on purchasing decisions, with a significance value of 0.000 < 0.05 and a t-count of 6.954 > t-table of 2.006. The coefficient of determination (R²) value of 0.477 indicates that 47.7% of the purchase decision can be explain by the TikTok content. These findings indicate that the audiovisual and narrative content of beauty influencers on TikTok plays an important role in shaping purchasing decisions, particularly among beauty education students. Keywords: Content, TikTok, @galih.makeupartis, Purchase decision, Product